Optimasi Papan Akustik Berbahan Pelepah Pisang, Eceng Gondok, dan Sekam Padi sebagai Peredam Kebisingan - Rahayu, Rahayu; Zulfian, Zulfian; Nurhanisa, Mega (JFT: Jurnal Fisika dan Terapannya, 2025)
Noise is a problem that often arises in the community. Several previous studies have found the potential of environmentally friendly natural materials to absorb sound. The purpose of this study was to determine the physical and mechanical properties of acoustic boards based on the composition of a mixture of banana leaf, water hyacinth, and rice husk materials and to analyze the effect of the mixture of banana leaf, water hyacinth, and rice husk material composition. The acoustic board was then tested for physical properties, mechanical properties, and sound absorption coefficient (α) using the one-microphone impedance tube method. Making acoustic boards with a material and adhesive ratio of 70%:30%, and a comparison of variations in the composition of banana stem, water hyacinth, and rice husk materials for sample A (60%: 10%: 0%), sample B (20%: 0%: 50%), sample C (0%: 10%: 60%), and sample D (20%: 10%: 40%). The results of the research on physical and mechanical properties meet the Indonesian National Standard (SNI) 01-4449-2006, namely the density value in all samples, moisture content in samples B, C, and D, and internal adhesive firmness in samples B and C. The test results of the sound absorption coefficient value of the acoustic board are categorized as being able to reduce noise by meeting the International Organization for Standardization (ISO) 11654 standard, which is greater than 0.15. The highest sound absorption coefficient value is obtained by sample D at a thickness of 1 cm with a sound absorption coefficient value of 0.287.